Growth Differentiation Factor 15 Regulates Oxidative Stress-Dependent Ferroptosis Post Spinal Cord Injury by Stabilizing the p62-Keap1-Nrf2 Signaling Pathway - Xia, Mingjie; Zhang, Qinyang; Zhang, Yanan; Li, Rulin; Zhao, Tianyu; Chen, Lingxia; Liu, Qiangxian; Zheng, Shengnai; Li, Haijun; Qian, Zhanyang; Yang, Lei (Frontiers in Aging Neuroscience, 2022)
Spinal cord injury (SCI) is a severe traumatic disorder of central nervous system (CNS) that causes irreversible damage to the nervous tissue. The consequent hemorrhage contributed by trauma induces neuronal ferroptosis post SCI, which is an important death mode to mediate neuronal loss. Growth differentiation factor 15 (GDF15) is a cytokine that regulates cell proliferation, differentiation and death. However, the specific role of GDF15 in neuronal ferroptosis post SCI remains unknown. In vitro, the expression of GDF15 was examined by real-time quantitative reverse-transcription polymerase chain reaction (qRT-PCR), western blotting (WB) and immunofluorescence (IF) staining. The level of ferroptosis was assessed by detection of lipid peroxidation, glutathione (GSH), iron content, reactive oxidative stress (ROS) and ferroptosis-associated proteins expression. In vivo, the mice were randomly assigned and performed for SCI. WB was utilized to measure the protein levels of GDF15, p62-Keap1-Nrf2 pathway and ferroptosis-related proteins. Ferroptosis after SCI was measured by IF. Neuronal death following SCI was evaluated using TUNEL staining and Nissl staining. Finally, locomotor function recovery was analyzed using the Basso Mouse Scale (BMS) and Louisville Swim Scale (LSS). The results showed that GDF15 was significantly increased in neuronal ferroptosis both in vitro and in vivo. Besides, silencing GDF15 aggravated ferroptosis, which can be rescued by adding the recombinant GDF15 (rGDF15). GDF15-mediated inhibition of neuronal ferroptosis is through p62-dependent Keap1-Nrf2 pathway. In vivo, knockdown of GDF15 inhibited p62-Keap1-Nrf2 pathway and aggravated ferroptosis post SCI. Furthermore, silencing GDF15 significantly exacerbated the death of neurons and restrained locomotor recovery in SCI mice. In conclusion, GDF15 effectively alleviated neuronal ferroptosis post SCI via p62-Keap1-Nrf2 signaling pathway and promoted locomotor recovery of SCI mice.